2021
DOI: 10.3390/ani11113089
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning-Based Automatic Monitoring of Pigs’ Physico-Temporal Activities at Different Greenhouse Gas Concentrations

Abstract: Pig behavior is an integral part of health and welfare management, as pigs usually reflect their inner emotions through behavior change. The livestock environment plays a key role in pigs’ health and wellbeing. A poor farm environment increases the toxic GHGs, which might deteriorate pigs’ health and welfare. In this study a computer-vision-based automatic monitoring and tracking model was proposed to detect pigs’ short-term physical activities in the compromised environment. The ventilators of the livestock b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In terms of behavior tracking, Alameer et al (2020) adopted the Faster R-CNN and YOLOv2 as the detectors and DeepSORT as the tracker to overcome illumination changes and the occlusions of pigs in the commercial environment. In addition, a deep-learningbased pig posture and locomotion activity detection and DeepSORT tracking algorithms were designed to measure pig behavior changes in an experimental pig barn at different greenhouse gas (GHG) levels [18]. These approaches were good at detection and tracking behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of behavior tracking, Alameer et al (2020) adopted the Faster R-CNN and YOLOv2 as the detectors and DeepSORT as the tracker to overcome illumination changes and the occlusions of pigs in the commercial environment. In addition, a deep-learningbased pig posture and locomotion activity detection and DeepSORT tracking algorithms were designed to measure pig behavior changes in an experimental pig barn at different greenhouse gas (GHG) levels [18]. These approaches were good at detection and tracking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…A probabilistic tracking-by-detection method was proposed, which first used a fully convolutional detector to detect visible key points of individual pigs and then tracked individual animals in a group setting [17]. A deep-learning-based pig posture and tracking algorithm were designed to measure those behavior changes in an experimental pig barn at different greenhouse gas (GHG) levels [18]. However, pig behavior detection and tracking still face some difficulties, such as target occlusion, varying light, overlapping, and error IDs of tracks in tracking [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Integrating gas sensors with ventilation systems helps control the indoor climate and maintain a healthy environment for animals and workers. High carbon dioxide CO 2 levels can pose a suffocation risk [ 13 , 14 ]. Using mechanisms that capture spatial–temporal correlations and dependencies among diverse data streams has proven highly effective.…”
Section: Introductionmentioning
confidence: 99%
“…Wang M et al [23] optimized FairMOT with a deep learning algorithm, realizing the recognition and tracking of reappearing pig individuals and improving the accuracy of multi-target recognition and tracking. Bhujel A et al [24] proposed a deep-learning-based pig individual and motion state detection and tracking algorithm and found that the YOLOv4 detector combined with the deep sorting tracking algorithm improves performance in pig multi-object detection and tracking. Zhang L et al [25] proposed a method for individual detection and tracking of live pigs that achieves a recognition accuracy of 94.72% and a recall rate of 94.74%, providing appearance features for the tracker.…”
Section: Introductionmentioning
confidence: 99%